2019
DOI: 10.1111/1365-2745.13187
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition reduced ecosystem stability regardless of its impacts on plant diversity

Abstract: Global environmental changes are altering ecosystem stability, sometimes by altering biodiversity. For example, by driving grassland plant species loss, nitrogen (N) addition can reduce ecosystem stability. In other cases, however, N addition may alter productivity and ecosystem stability, by increasing the dominance of particularly productive or stable species. We examined how N addition affected plant diversity, productivity and the temporal stability of productivity in an 8‐year grassland experiment. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 59 publications
9
56
1
Order By: Relevance
“…Moreover, community destabilization associated with enrichment was not revealed by diversity measures, only by increased turnover in species' relative abundances over time (see also Liu et al, 2019). These results, combined with other terrestrial and marine studies showing that effects varied across time, abiotic drivers or scales of organization (e.g.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, community destabilization associated with enrichment was not revealed by diversity measures, only by increased turnover in species' relative abundances over time (see also Liu et al, 2019). These results, combined with other terrestrial and marine studies showing that effects varied across time, abiotic drivers or scales of organization (e.g.…”
Section: Discussionsupporting
confidence: 54%
“…Varied effects, such as positive, negative and even no effects of N addition on plant communities, have been observed in numerous ecosystems (e.g. Liu et al, ; Niu et al, ; Su et al, ; Xu et al, ). For instance, in a semi‐arid grassland of northern China, Niu et al () found that plant community stability was significantly reduced at N addition levels from 4.6 to 13.8 g N m −2 year −1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, atmospheric N deposition is estimated to increase from 0.05 to 2.0 g N m −2 year −1 world‐wide (Galloway et al, ) and has increased from 1.3 to 2.1 g N m −2 year −1 in China (Liu et al, ). An increasing number of studies have found that N deposition could lead to increases in ANPP but declines in plant diversity and ecosystem stability (Clark & Tilman, ; Liu et al, ; Xu, Jiang, & Zhou, ). Furthermore, the response of plant communities to N addition could be mediated by environmental factors, particularly precipitation (Reichmann, Sala, Peters, & Debra, ; Tian et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very interesting study, Liu et al [74] used structural equation modelling to identify the likely causal mechanisms linking fertilization, biodiversity and ES in a Chinese grassland ( Figure 3). They found evidence for both direct and biodiversity-mediated effects of N-addition on two ecosystem services: aboveground net primary production and ecosystem stability.…”
Section: What Can We Learn From Experiments and Field Observations?mentioning
confidence: 99%